2010
DOI: 10.4102/sajcd.v57i1.47
|View full text |Cite
|
Sign up to set email alerts
|

Young children with fetal alcohol spetrum disorder - communication profiles

Abstract: The aim of the article is to describe the communication profiles of five young children with fetal alcohol spectrum disorder (FASD) from 4 to 58months of age. A collective case-study design following a quantitative and descriptive approach was used to describe the communication profilesof the participants. The results are described according to the participants’ case histories and a four-level early communication assessment framework.The significant findings were that all participants were in foster care, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
2
5
0
6
Order By: Relevance
“…28 Another study examining children between the ages of 4 and 58 months found that all participants with FASD showed language impairment, communication delay, verbosity, and some processing disorder. 29 These results were consistent with another study on preschool children, which also found that children with FASD had significantly impaired communication skills. 4…”
Section: Executive Functioning and Attention -supporting
confidence: 90%
“…28 Another study examining children between the ages of 4 and 58 months found that all participants with FASD showed language impairment, communication delay, verbosity, and some processing disorder. 29 These results were consistent with another study on preschool children, which also found that children with FASD had significantly impaired communication skills. 4…”
Section: Executive Functioning and Attention -supporting
confidence: 90%
“…This fact was also described in a prior study 33 . Studies with cases made up of younger individuals tend to report less-compromised clinical pictures than those with school-aged individuals 16,18 .…”
Section: Figure 2-synthesis Of Compiled Articles On Spoken Language Isupporting
confidence: 85%
“…Studies with cases made up of younger individuals tend to report less-compromised clinical pictures than those with school-aged individuals 16,18 . However, the use of development scales has allowed researchers to identify delays of, at least, six months by individuals with FASD compared with their peers of the same chronological age and who have not been exposed to alcohol during pregnancy 16,18,20,21,33,34 . One aspect that must be considered when proposing a design for a study in the area of spoken language, including individuals in preschool age, is the relatively lower number of instruments available for this assessment, when compared with the instruments available for school-aged population.…”
Section: Figure 2-synthesis Of Compiled Articles On Spoken Language Imentioning
confidence: 99%
“…In addition, OPD may be the result of structural impairments because of an underlying genetic condition (Blake & Hudson, 2017). High-risk infants in South Africa may be prenatally exposed to alcohol and other substance abuse (De Beer, Kritzinger, & Zsilavecz, 2010; Okoroh et al, 2017). Exposure to the human immunodeficiency virus (HIV) and antiretroviral treatment are additional risks in lower-middle-income countries (LMICs) such as South Africa that may lead to subtle neurodevelopmental concerns influencing feeding (Salihu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%